Analisis Faktor Faktor yang Menyebabkan Terjadinya Gagal Klaim Asuransi pada PT Prudential Life Assurance Cabang Binjai - Nurul Hafizah Nst; Fauzi Arif Lubis (Universitas Muhammadiyah Surabaya, 2023)
AbstractInsurance is a protection mechanism between the insurance company that binds itself to the insured where the insurer receives several premiums paid by the insured in the event of a loss or risk in the future. With the official payment paid every month, it will make it easier for the insured (customer) to carry out insurance activities. However, in its activities, not every insured person meets the requirements to receive compensation at the time of filing a claim. From this background, there is a formulation of the problem, namely the factors that cause rejection or failure of claims made by the insured and what solutions the company can provide to the insured. This research was conducted at PT. Prudential Life Assurance Binjai branch using a qualitative approach. The types of data used in this research are primary data and secondary data. Primary data obtained through interviews and secondary data obtained through journals, articles that match the object. The results of the study show that the causative factors for failed claims to customers are due to insurance policies that have lapsed so that companies refuse to submit claims. Meanwhile, to get compensation, the insured's policy must remain active so that claims can be made against the insured.Keywords : Factors, Claim Failure, Insurance